Melanin pigmentation gives rise to black spots on the wings of the silkworm Bombyx mori. (August 2016) - Ito, Katsuhiko; Yoshikawa, Manabu; Fujii, Takeshi; Tabunoki, Hiroko; Yokoyama, Takeshi
Graphical abstract: Highlights: The black pigment of the Ws mutant exists in the scales of the wing. The black pigment of the Ws mutant is melanin. Melanin-related genes are involved in the black pigment of the Ws mutant. Dopa-melanin and dopamine-melanin are related to the black pigment of the Ws mutant. Abstract: Several mutants of the silkworm Bombyx mori show body color variation at the larval and adult stages. The Wild wing spot ( Ws ) mutant exhibits a phenotype in which the moth has a spot on the apex of the forewing. In this study, we investigated this trait to elucidate the molecular mechanism underlying the color pattern. Microscopy of the black spot of Ws mutants showed that the pigment emerges in the scales of the wing, and accumulation of the pigment becomes strong just before eclosion. We next examined the relationship between the black spot of the Ws mutant and melanin. The spectrophotometry using alkaline extracts from the black spot in the wing showed the highest absorption intensity at 405 nm, which is the absorbance wavelength of melanin. Moreover, inhibition assays for enzymes implicated in melanin synthesis using 3-iodo-l -tyrosine (a tyrosine hydroxylase inhibitor) and L-α-methyl-DOPA (a dopa decarboxylase inhibitor) revealed that treatment with each inhibitor disrupted the pigmentation of the wing of the Ws mutant. On the basis of these results, we analyzed the expression pattern of five genes involved in melanin formation, and found that the expression levels of yellow and laccase2 were increased just before pigmentation, whereas those of DDC, tan, and TH were increased when the apex of the wing turned black. These results showed that melanin pigmentation gives rise to the black spot on the wing.